Draw-A-Science-Comic: Alternative prompts and the presence of danger - Lamminpää, Jaakko; Vesterinen, Veli-Matti (LUMAT: International Journal on Math, Science and Technology Education, 2020)
The early years of primary school are important in shaping how children see scientists and science, but researching younger children is known to be difficult. The Draw-A-Scientist Test (DAST), in which students are asked to draw a scientist, has been one of the most popular ways to chart children’s conceptions of scientists and science. However, DAST tends to focus mainly on children’s conceptions about the appearance of scientists. To focus more on children’s conceptions of scientific activities as well as the emotions and attitudes associated with science, the Draw-A-Science-Comic test (DASC) was recently introduced. This study compares three alternative DASC prompts for two age groups of respondents (8- to 10-year-olds and 10- to 13-year-olds). The prompts asking students to draw a comic or a set of pictures produced significantly more sequential storytelling and depictions of science related emotions and attitudes than the prompt asking students to depict a story. The depictions of elements of danger, such as accidents and hazards in the laboratory, were also frequent in drawings with sequential storytelling. A more detailed analysis of the depictions showed that the frequency of elements of danger was closely associated with depictions of activity especially in the field of chemistry. For example, several comics included failed chemical experiments leading to explosions. Although depictions of danger are sometimes interpreted as a negative conception, in the children’s drawings the explosions and overflowing flasks were often seen also as a source of excitement and joy. Based on the result of this study, the use of DASC seems a suitable way for charting children’s conceptions of scientific activities as well as the emotions and attitudes associated with science from the early years of primary education until the beginning of secondary education.